Currency board or central bank? Lessons from the Irish pound’s link with sterling, 1928-79 - P. HONOHAN (PSL Quarterly Review, 2013)
The resurgence of interest in currency boards prompts reconsideration of one of the Irish experience. The authors evaluate the institutional arrangements which underpinned the Irish pound for a half-century. While the regime did have a credibility which led to low interest rates and a degree of price stability, its resilience was partly due to the large additional foreign reserves held by the private banking system and to the fact that the sterling proved not to be a very strong currency. However, an attempt in 1955 to evade the interest rate discipline of the regime was quickly punished, with far-reaching policy consequences.